The EFFECT OF CHICKEN EGG SHELL POWDER ON THE GROWTH AND YIELD OF LEAF ONION (ALLIUM FISTULOSUM) - Mardia Apriansi; Adnan Adnan; Merri Sri Hartati (Fakultas Pertanian Universitas Ratu Samban, 2022)
Rejang Lebong has local commodities, one of which is green onion, because the topographic and geographical conditions of Rejang Lebong are suitable for the growth of leeks. The leek plants produced in the Rejang Lebong area are diverse, where there are leek plants that have a soft stem texture. In the cultivation of leeks, most of the farmers in Rejang Lebong still use inorganic fertilizers to support their agricultural production, this situation if carried out in the long term can have a negative impact on the surrounding environment, especially on agricultural land. Rejang Lebong is a developing city that has many home industries such as the cake industry, restaurants, bakeries, noodle stalls and egg martabak that use eggs as raw materials, so there is a lot of egg shell waste that is not utilized and just thrown away and has an impact on the environment. environmental pollution such as bad smell. The purpose of this study was to determine the effect of broiler eggshell powder on the growth and yield of leek (Allium fistulosum), and what dose was effective for wet weight of leek (Allium fistulosum). This research is a field experiment research using a completely randomized design with 1 factor and 7 treatments, 3 replications, data analysis using analysis of variance (ANOVA). The results showed that there was an effect of egg shell powder on the growth and yield of leek (Allium fistulosum) and the effective dose for growth and yield of leek (Allium fistulosum) was P6 (55 grams).